2009
DOI: 10.1016/j.landusepol.2008.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Application of an ecosystem function framework to perceptions of community woodlands

Abstract: a b s t r a c tOwners, local residents, government, and conservation organisations can express divergent preferences in the development and management of local woodlands. The perceptions of these four groups were examined, in the context of three community woodlands in Eastern England, using an ecosystem function framework. In a pilot study, residents were able to allocate a relative importance to woodland ecosystem services which were then related to "regulation", "habitat", and "production" or "information" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 21 publications
3
49
1
7
Order By: Relevance
“…Our finding regarding the importance of ecosystem services is in line with other studies showing that rural communities show high appreciation toward provisioning ecosystem services (Iftekhar and Takama 2008, Agbenyega et al 2009, Martín-López et al 2012, in contrast to urbanized communities who mostly appreciate the aesthetic and recreational values of landscapes (Martín-López et al 2012, Plieninger et al 2013. Industrial activity and opportunities for stable jobs in the study region are poor; therefore the majority of people still largely depend on provisioning ecosystem services in their everyday lives (Fischer et al 2012, Mikulcak et al 2013.…”
Section: Discussionsupporting
confidence: 89%
“…Our finding regarding the importance of ecosystem services is in line with other studies showing that rural communities show high appreciation toward provisioning ecosystem services (Iftekhar and Takama 2008, Agbenyega et al 2009, Martín-López et al 2012, in contrast to urbanized communities who mostly appreciate the aesthetic and recreational values of landscapes (Martín-López et al 2012, Plieninger et al 2013. Industrial activity and opportunities for stable jobs in the study region are poor; therefore the majority of people still largely depend on provisioning ecosystem services in their everyday lives (Fischer et al 2012, Mikulcak et al 2013.…”
Section: Discussionsupporting
confidence: 89%
“…Agbenyega et al (2009) suggested that regulating ESs may be overlooked because of the invisible character of these services. People may need better understanding of such services in order to appreciate them.…”
Section: Discussion Linking Use Awareness and Valuation Of Essmentioning
confidence: 99%
“…Agbenyega et al, 2009;Bennett et al, 2010;Escobedo et al, 2011;Escobedo et al, 2011;Gómez-Baggethun and Barton, 2013;Limburg et al, 2010;Lyytimäki, 2014;Lyytimäki and Sipilä, 2009;Lyytimäki et al, 2008;Ma et al, 2015;Roy et al, 2012;Zhang et al, 2007. Ango et al, 2014;Escobedo et al, 2011;Gómez-Baggethun and Barton, 2013;Lyytimäki, 2014;Lyytimäki and Sipilä, 2009;Lyytimäki et al, 2008;Roy et al, 2012;.…”
Section: Ecosystem Disservices (Eds)unclassified